2014
DOI: 10.1002/jclp.22102
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Intervention for Child Abuse Survivors: A 2.5-Year Follow-Up

Abstract: Objective: The present study reports on the long-term effects of a mindfulness-based stress reduction (MBSR) program for adult survivors of childhood sexual abuse. Method: Of the study participants, 73% returned to the clinic for a single-session follow-up assessment of depression, posttraumatic stress disorder (PTSD), anxiety, and mindfulness at 2.5 years. Results: Repeated measures mixed regression analyses revealed significant long-term improvements in depression, PTSD, anxiety symptoms, and mindfulness sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 32 publications
0
53
0
Order By: Relevance
“…Another study investigating treatment with MBSR modified to emphasize safety and positive growth experiences found particularly large reductions on self-reported PTSD avoidance/numbing symptoms and re-experiencing, hyperarousal, depression and anxiety symptoms among women with PTSD as a result of childhood sexual abuse. 134 These gains were maintained 2.5 years later, 130 showing the potential long-term utility of MBSR. Moreover, these studies reported low drop-out rates (10%-16%), suggesting high treatment acceptability.…”
Section: Mindfulness-based Stress Reduction For Ptsdmentioning
confidence: 93%
See 3 more Smart Citations
“…Another study investigating treatment with MBSR modified to emphasize safety and positive growth experiences found particularly large reductions on self-reported PTSD avoidance/numbing symptoms and re-experiencing, hyperarousal, depression and anxiety symptoms among women with PTSD as a result of childhood sexual abuse. 134 These gains were maintained 2.5 years later, 130 showing the potential long-term utility of MBSR. Moreover, these studies reported low drop-out rates (10%-16%), suggesting high treatment acceptability.…”
Section: Mindfulness-based Stress Reduction For Ptsdmentioning
confidence: 93%
“…Additionally, several single-arm uncontrolled trials reported significant improvements in PTSD and related symptomatology following MBSR treatment among veterans 129,132 and victims of interpersonal or developmental trauma. 131,134,139 Importantly, across these studies, treatment gains were largely maintained at follow-up ranging from 1 month to 2.5 years 129,130,132,134,138,139 (but see the studies by Kearney and colleagues 133 and Niles and colleagues 137 ). Critically, the study by Niles and colleagues, 137 which did not report maintained improvement at follow-up, used a telehealth approach, suggesting that more intensive, inperson treatment may be necessary to maintain treatment gains.…”
Section: Mindfulness-based Approaches In the Treatment Of Ptsdmentioning
confidence: 95%
See 2 more Smart Citations
“…Mindfulness-based interventions, such as Acceptance and Commitment Therapy (ACT) (A-Tjak et al 2015;Ost 2014), are among those that are rapidly gaining in popularity to help decrease a variety of mental health problems in children and adolescents (Tovote et al 2014;Broderick and Jennings 2012;Cotton et al 2015;Zoogman et al 2015), as well as in children, adolescents and adult survivors of childhood maltreatment (Kimbrough et al 2010;Caldwell and Shaver 2015;Lanktree et al 2012;Mannarino et al 2012). Mindfulness training has been found to help diminish symptoms of depression, anxiety, post-traumatic stress disorder (PTSD), sexual dysfunction and general distress in adult women reporting CSA (Earley et al 2014;Kimbrough et al 2010;Brotto et al 2012) and to reduce behavioural, externalized and internalized problems among youth reporting various types of childhood maltreatment (Swart and Apsche 2014).…”
Section: Introductionmentioning
confidence: 99%